022 Novel perfusion CMR reference standard for the objective diagnosis of microcirculatory dysfunction – validation against prognostic invasive markers of coronary physiology. (3rd April 2017) - Liu, Alexander; Wijesurendra, Rohan S; Liu, Joanna M; Forfar, John C; Channon, Keith M; Piechnik, Stefan K; Neubauer, Stefan; Kharbanda, Rajesh K; Ferreira, Vanessa M
Abstract : Objectives: In patients with angina and non-obstructive coronary arteries, abnormal index of microcirculatory resistance (IMR ≥23) and coronary flow reserve (CFR ≤2.0) confer adverse clinical outcomes. We hypothesised that these prognostic invasive markers of microcirculatory dysfunction are related to impaired downstream myocardial perfusion reserve (MPR) as assessed by CMR. Methods: 60 subjects (20 patients with angina and non-obstructive coronary arteries, 20 patients with obstructive coronary artery disease [CAD] and 20 normal controls) underwent CMR for the assessment of LV function (cines), ischaemia (adenosine stress and rest perfusion) and infarction (LGE). During invasive coronary angiography, patients with non-obstructive coronary arteries had fractional flow reserve (FFR), CFR and IMR measured in all 3 coronary arteries (60 vessels), while patients with obstructive CAD had FFR measured in the obstructive coronary artery only (20 vessels). CMR images were analysed blinded to clinical information and invasive coronary data. MPR was derived as the ratio between stress and rest myocardial perfusion signal intensity upslope gradients, normalised to LV blood signal intensity. Results: Myocardium with LGE was excluded. Non-infarcted myocardium downstream obstructive coronary arteries (FFR <0.80) had lower MPR compared to controls (1.3±0.4 vs 1.9±0.3, p<0.001). Downstream of non-obstructive coronary arteries (FFR >0.80), myocardium with normal microcirculatory function (normal IMR and CFR) had similar MPR compared to controls (1.9±0.2 vs 1.9±0.3, p=0.83). Myocardium with prognostic microcirculatory dysfunction (IMR ≥23 and CFR≤2.0) had significantly impaired MPR (1.3±0.3, p<0.001); further, the degree of impairment in MPR was similar to ischaemic myocardium downstream obstructive coronary arteries (MPR 1.3±0.3 vs 1.3±0.4, p=0.73; Figure 1 ). On ROC analysis, a threshold of MPR=1.4 detected prognostic microvascular dysfunction (IMR ≥23 and CFR≤2.0) in non-obstructive coronary arteries with specificity 97%, sensitivity 81%, and accuracy 89% (AUC 0.95±0.02, Figure 2 ). Conclusions: In patients with angina and non-obstructive coronary arteries, an MPR threshold of 1.4 on perfusion CMR accurately detects prognostic invasive markers of microcirculatory dysfunction. This novel MPR threshold can now be used to objectively diagnose microvascular angina in clinical practice and guide disease management.